Developmental Personality Types From Childhood to Adolescence: Associations With Parenting and Adjustment. Issue 6 (28th March 2013) - de Haan, Amaranta D.; Deković, Maja; van den Akker, Alithe L.; Stoltz, Sabine E. M. J.; Prinzie, Peter
Abstract : This study examined whether changes in children's self‐reported Big Five dimensions are represented by (developmental) personality types, using a cohort‐sequential design with three measurement occasions across 5 years (four cohorts, 9–12 years at T1; N  =   523). Correlates of, and gender differences in, type membership were examined. Latent class growth modeling yielded three personality types: Resilients (highest initial levels on all Big Five), Overcontrollers (lowest Extraversion, Emotional Stability, Imagination), and Undercontrollers (lowest Benevolence, Conscientiousness). Gender differences in type membership were small. Warm parenting, but not overreactive discipline, in childhood was associated with type membership. The types differed in adjustment problems by the end of middle adolescence. Personality change more likely occurs at the level of dimensions within types than in type membership.